Decoupled multiuser code-timing estimation for code-division multiple-access communication systems. - Hongbin Li
We present herein a decoupled multiuser acquisition (DEMA) algorithm for code-timing estimation in asynchronous code-division multiple-access (CDMA) communication systems. The DEMA estimator is an asymptotic (for large data samples) maximum-likelihood method that models the channel parameters as deterministic unknowns. By evoking the mild assumption that the transmitted data bits for all users are independently and identically distributed, we show that the multiuser timing estimation problem that usually requires a search over a multidimensional parameter space decouples into a set of noniterative one-dimensional problems. Hence, the proposed algorithm is computationally efficient. DEMA has the desired property that, in the absence of noise, it obtains the exact parameter estimates even with a finite number of data samples which can be heavily correlated. Another important feature of DEMA is that it exploits the structure of the receiver vectors and, therefore, is near-far resistant. Numerical examples are included to demonstrate and compare the performances of DEMA and a few other standard code-timing estimators
Keywords: CDMA communication; DEMA algorithm; Channel parameters; Code-division multiple-access communication systems; Decoupled multiuser code-timing estimation; Maximum-likelihood method; Multiuser timing estimation problem; Noniterative one-dimensional problems; Parameter estimates; Receiver vectors; Transmitted data bits